2000
DOI: 10.1007/s00585-000-1067-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined ESR and EISCAT observations of the dayside polar cap and auroral oval during the May 15, 1997 storm

Abstract: Abstract. The high-latitude ionospheric response to a major magnetic storm on May 15, 1997 is studied and dierent responses in the polar cap and the auroral oval are highlighted. Depletion of the F 2 region electron density occurred in both the polar cap and the auroral zone, but due to dierent physical processes. The increased recombination rate of O + ions caused by a strong electric ®eld played a crucial role in the auroral zone. The transport eect, however, especially the strong upward ion¯ow was also of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…It could be related to the following. Despite the fact that there is energy input of the penetration of the electric field, which can cause joule heating in the ionosphere (Liu et al, 2000), there has been speculation about an additional source of energy at lower latitudes during disturbances. In particular, Noël and Pröllss (1993) suggested that heating by a neutralized ring current could be the possible heat source at equatorial and tropical latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…It could be related to the following. Despite the fact that there is energy input of the penetration of the electric field, which can cause joule heating in the ionosphere (Liu et al, 2000), there has been speculation about an additional source of energy at lower latitudes during disturbances. In particular, Noël and Pröllss (1993) suggested that heating by a neutralized ring current could be the possible heat source at equatorial and tropical latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Prölss, 1995;Mikhailov and Schlegel, 1998;Liu et al, 2000). Several mechanisms could be responsible for these depletions.…”
Section: High Latitudesmentioning
confidence: 99%
“…We can see that enhancements in electron density around 09:10 UT and 09:50 UT are accompanied by a remarkable increase in electron temperature, suggesting their association with local soft particle precipitation. It has been shown in our previous paper (Liu et al, 2000) that these two electron enhancements are peak-to-peak correlated with a large pulselike increase in solar wind dynamic pressure by pressurecontrolled soft particle precipitation. On the other hand, there is no remarkable increase in electron temperature accompanying the "blob" between 10:40 UT to 11:10 UT.…”
Section: Evidence Of Strong Dayside Aurora Near Eiscat By Polar Uvimentioning
confidence: 53%
“…16.0 • E) were in operation and caught the storm simultaneously during its main phase at the dayside sector. In our previous paper (Liu et al, 2000), it was indicated that, according to calculations by means of the T96-01 magnetic field model (Tsy- ganeko, 1996), ESR was in the dayside polar cap during the main phase and the beginning of the recovery phase of the 15 May 1997 storm, while EISCAT was in the dayside auroral oval or on its poleward boundary, being in agreement with the UV images taken from the ultraviolet imager (UVI) on board the POLAR satellite. This provides a valuable opportunity to investigate storm effects in the dayside auroral oval and in the polar cap regions simultaneously.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation